TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENIPUAN (STUDI KASUS PERKARA NOMOR. 153/PID.B/2013/PN.BKN) - Haposan, Indra; Lestari, Rika; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Law is actually formed and applied as a means to provide protection to everyone equitably. One example of crime that are rampant fraud is a criminal offense with a variety of modes. Criminal cases of fraud committed by the defendant named Lukman DT Hero Member with fraud crimes mode of sale of land belonging to another person completely unknown to the owner of the land (Tini). Defendant together with SIJAS (DPO) to cooperate to sell land belonging to Tini of 8.5 hectares with a sales value of Rp. 323 668 800 (Three hundred and twenty-three million six hundred sixty-six-eight thousand eight hundred dollars) purchased by Heri (witness). The defendant in the crime action together with the power of attorney SIJAS making false sales engineering and false SKGR letter, so Heri believe that the letter is original from the landowner (Tini)In this study the authors, set the following principal problems of proving the crime of fraud in the case number 153 / Pid.B / 2013 / PN.BKN? and legal considerations judges How to criminal fraud in the case number 153 / Pid.B / 2013 / PN.BKN.In this writing, when viewed from the type of research that is classified as a normative legal research is research that is done by examining the law library materials related to the problem, whereas if seen from the nature of this research is descriptive research that explains in clear form sentences and detailed. From the research Evidence of criminal fraud in the sale of land case number 153 / Pid.B / 2013 / PN.BKN conducted with respect to evidence presented at the hearing conducted by the Public Prosecutor to present some witnesses as many as three (3 ) witnesses, documentary evidence and the testimony of the defendant who testified that the defendant has committed the crime of fraudulent sale of land belonging to someone else. While the comparison verdict against perpetrators of fraud in some cases, according to the author of the judge make a decision only as a punishment to the perpetrators who commit the offense is not to provide a deterrent effect both for the perpetrators and to those who want to commit criminal acts of fraud and selling land the.Keywords: Overview Yuridis- Crime-Fraud